Interrelationship Between Broadband NIRS Measurements of Cerebral Cytochrome C Oxidase and Systemic Changes Indicates Injury Severity in Neonatal Encephalopathy (2016)
Perinatal hypoxic ischaemic encephalopathy (HIE) is associated with severe neurodevelopmental problems and mortality. There is a clinical need for techniques to provide cotside assessment of the injury extent. This study aims to use non-invasive cerebral broadband near-infrared spectroscopy (NIRS) in combination with systemic physiology to assess the severity of HIE injury. Broadband NIRS is used to measure the changes in haemodynamics, oxygenation and the oxidation state of cytochrome c oxidase (oxCCO). We used canonical correlation analysis (CCA), a multivariate statistical technique, to measure the relationship between cerebral broadband NIRS measurements and systemic physiology. A strong relationship between the metabolic marker, oxCCO, and systemic changes indicated severe brain injury; if more than 60?% of the oxCCO signal could be explained by the systemic variations, then the neurodevelopmental outcome was poor. This boundary has high sensitivity and specificity (100 and 83?%, respectively). Broadband NIRS measured concentration changes of the oxidation state of cytochrome c oxidase has the potential to become a useful cotside tool for assessment of injury severity following hypoxic ischaemic brain injury.